Comparação do processo de regeneração natural em áreas com diferentes usos do solo - Colusso, Fabrício Schneider (2019)
Natural regeneration is fundamental for the recovery of degraded areas and maintenance of forests, because through it occurs the replacement of local species and the emergence of others, guaranteeing the continuity of ecological succession. In addition, it is through regeneration that forests recover from natural or anthropogenic events. The way in which the forest regenerates depends on mechanisms that help in the arrival of new propagules in the area and in the establishment of new individuals, such as: fruit production, seed bank, seedlings bank, presence of dispersers and chemical properties of the soil. With the monitoring of the regeneration and the mechanisms mentioned above, there is an answer about the functioning of the system and the development of the forest. The objective of this dissertation is to evaluate the mechanisms that act in the natural regeneration. In addition to natural regeneration, the following indicators were evaluated: seed rain, evaluation of the epiedaphic fauna, litter litter, presence of dispersing avifauna and chemical characterization of the soil. The study was carried out in a plot of 20 m x 45 m (900 m²) delimited within each study area. The natural regeneration was evaluated in three transects installed in each plot, and the rest of the indicators in places near the transects. The results showed that attributes as a better developed understorey combined with the 11 species cataloged in natural regeneration, especially Eugenia uniflora and Solanum mauritianum, indicate that area 2 is being recovered faster than the others. The accumulation of P.elliotti needles in area 1 may be a limiting factor, representing a barrier in the germination of arboreal species that will form the local natural regeneration in the future.The fact that the species E. bifida is the main colonizer in area 3, demonstrates its potential in the colonization of open areas and the resumption of forest succession, however, the presence of P. elliotti individuals in the area is a negative factor, demonstrating the potential of contamination of the species, which must be removed. The prevalence of species of birds of omnivorous habit in the three study areas is a positive factor, indicating that generalist species persist in altered environments, being important in the dispersion of propagules that will form the natural regeneration in the future. The vegetation cover influenced the populations of the fauna and fauna, being yielded by the species P. elliotti and E. saligna restrictive, impairing the abundance of most of the orders found. The leaves and melliferous characteristics of the species E. bifida were favorable for a better distribution among the orders in area 3. Another factor that interfered in the abundance was soil moisture, being favorable for the predominance of individuals of the order colembola in areas 1 and 2. In general, the soils of the three areas did not present very different values for the soil chemical indicators, presenting acidic pH typical of subtropical regions.